Metabolic Engineering of Saccharomyces cerevisiae for Enhanced Carotenoid Production From Xylose-Glucose Mixtures - Su, Buli; Song, Dandan; Zhu, Honghui (Frontiers in Bioengineering and Biotechnology, 2020)
Co-utilization of xylose and glucose from lignocellulosic biomass is an economically feasible bioprocess for chemical production. Many strategies have been implemented for efficiently assimilating xylose which is one of the predominant sugars of lignocellulosic biomass. However, there were few reports about engineering Saccharomyces cerevisiae for carotenoid production from xylose-glucose mixtures. Herein, we developed a platform for facilitating carotenoid production in S. cerevisiae by fermentation of xylose-glucose mixtures. Firstly, a xylose assimilation pathway with mutant xylose reductase (XYL1m), xylitol dehydrogenase (XYL2) and xylulokinase (XK) was constructed for utilizing xylose. Then, introduction of phosphoketolase (PK) pathway, deletion of Pho13 and engineering yeast hexose transporter Gal2 were conducted to improve carotenoid yields. The final strain SC105 produced a 1.6-fold higher production from mixed sugars than that from glucose in flask culture. In fed-batch fermentation with continuous feeding of mixed sugars, carotenoid production represented a 2.6-fold higher. To the best of our knowledge, this is the first report that S. cerevisiae was engineered to utilize xylose-glucose mixtures for carotenoid production with a considerable high yield. The present study exhibits a promising advantage of xylose-glucose mixtures assimilating strain as an industrial carotenoid producer from lignocellulosic biomass.